2020
DOI: 10.1259/bjr.20190407
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial chemoembolization for pulmonary or mediastinal metastases from hepatocellular carcinoma

Abstract: Objective: To evaluate the feasibility, efficacy and safety of transcatheter arterial chemoembolization (TACE) with HepaSphere for patients with pulmonary or mediastinal metastases from hepatocellular carcinoma (HCC). Methods: Between June 2009 and January 2018, 14 patients with pulmonary or mediastinal metastases from HCC were treated with TACE with a combination of 1–3 chemotherapeutic drugs followed by HepaSphere embolization. As first end point, local tumor response and adverse events were evaluated after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Vascular 3-D images effectively support selecting small branches arising from the aorta ( 30 ). Selective arterial contrast infusion CT is crucial in estimating individual arterial supply to the target lesions ( 11 , 26 , 27 ).…”
Section: Present Understanding On Arterial Management Of Lung Cancermentioning
confidence: 99%
“…Vascular 3-D images effectively support selecting small branches arising from the aorta ( 30 ). Selective arterial contrast infusion CT is crucial in estimating individual arterial supply to the target lesions ( 11 , 26 , 27 ).…”
Section: Present Understanding On Arterial Management Of Lung Cancermentioning
confidence: 99%
“…Not unexpectedly, it has been recently studied in patients with hepatocellular carcinoma to treat intrathoracic metastatic spread (77). This technique may be employed either alone or prior to ablation in a multimodality strategy, with the aim to improve local disease control by eliminating eventual micrometastasis and reducing the need for a larger safety margin during subsequent percutaneous ablation (63,78).…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of the procedure, the ethiodized oil and mitomycin were pumped through the three-way stopcock at vice versa. Previous studies have shown that lung tumors with more enhancement at arteriography are more likely to respond to chemoembolization, and a thorough search for bronchial and nonbronchial systemic arteries supplying the tumor is critical for achieving a good response after bronchial artery TACE (7,9,10). However, none of the previous studies have examined both the bronchial and pulmonary arteries.…”
Section: Ethiodized Oil and Mitomycin Emulsion Preparationmentioning
confidence: 99%